Effectiveness of Integrated Maternal Nutrition Intervention Package on Birth Weight in Rwanda - Habtu, Michael; Agena, Alemayehu Gebremariam; Umugwaneza, Maryse; Mochama, Monica; Munyanshongore, Cyprien (Frontiers in Nutrition, 2022)
Inadequate maternal nutrition before and during pregnancy is the principal risk factor for poor fetal development subsequently resulting in low birth weight (LBW) and poor child growth. Most studies focus on the impact of interventions after birth while LBW is a precursor for poor child growth. Moreover, only a few interventions consider integrated nutrition service packages. There is therefore limited evidence whether integrated maternal nutrition interventions have positive effect on birthweight. Thus, a post program quasi experimental evaluation was carried out to determine the effectiveness of integrated maternal nutrition intervention package on low birth weight in Rwanda. A total of 551 mother-baby pairs for intervention and 545 of controls were included in the analysis. Data regarding socio-demographic, maternal anthropometric parameters and dietary diversity were collected using structured questionnaire. Birth weight was assessed right after delivery within 24 hours. Logistic regression, linear regression and path analysis were fitted to determine the effectiveness of the intervention on birth weight. The study found out that the intervention reduced LBW by 66.99% (p<0.001) and increased average birth weight by 219 grams (p<0.001). Logistic regression identified reduced risk of LBW among the intervention group (AOR=0.23; 95%CI = 0.12-0.43; p<0.001). It was also observed that direct effect of the intervention on birth weight was 0.17 (β =0.17; p <0.001) and the main indirect mediator was maternal MUAC (β =0.05; p<0.001). Moreover, maternal passive smoking exposure and MUAC <23cm were found risk factors for LBW. This study has demonstrated that integrated maternal nutritional intervention package can significantly reduce LBW. Therefore, integrated maternal nutrition intervention package during pregnancy should be considered to improve birth weight.